SKIN SEGMENTATION AND SKULL SEGMENTATION FOR MEDICAL IMAGING - Tjandra, Eric Yogi; Liliana, ,; Kheng, Leow Wee (Institute of Research and Community Outreach - Petra Christian University, 2014)
In this paper aims we present tools for medical imaging applications to do skin and skull segmentation in a short time. The desired output for skin segmentation is a 3D visualization of the facial skin without any cavities or holes inside the head, while skull segmentation aims to create a 3D visualization of the skull bones. The algorithm used for skin segmentation is thresholding the image, extracting the largest connected component, and holefilling to fill the unnecessary holes. As for the skull segmentation, the process is done by removing the spines which is connected to the skull, and then extracting the largest connected component. Afterwards, mesh generation is done to produce the 3D objects from the processed images. This mesh generation process is done using the marching cubes algorithm. The testing results show that the skin and skull segmentation process will work well when there are no other objects that are connected to the skin or the skull. Skin segmentation process takes a significant amount of time, primarily caused by the holefilling process.